Transcendental Phenomenological Study on Faculty Turnover in a Faith-Based Higher Education Institution in the Philippines - Bacolod, Annalyn; Saban, Gracel Ann; Mostaza, Lolina (12th International Scholars Conference 2025, 2026)
Employing Husserl’s transcendental phenomenology research design, this study explores the lived experiences of faculty who resigned or accepted a job offer in another institution in a faith-based higher educational institution in the Philippines. Five participants were purposively sampled and presented in pseudonyms. A semi-structured interview guide was developed and utilized in the light of the research questions. One-on-one interviews through Zoom were guided by the relevant ethical considerations. Reflexivity was applied. Data were transcribed and analyzed employing Moustaka’s (1994) transcendental phenomenological procedures for data analysis. Three central themes emerged: Fulfillment of a Higher Purpose or Calling, where participants followed God’s leading into new mission fields; Further Growth, Development, and Actualization, reflecting the pursuit of professional challenge, skill expansion, and self-actualization; and Common Challenges Faced, including heavy workloads, limited support, and uneven policy application. Contextually, participants recalled strong collegial bonds, a nurturing spiritual environment, and meaningful student engagement, while envisioning fairer policies, greater inclusivity, and more robust professional development. The study underscores how spiritual calling, growth needs, and workplace realities intertwine in shaping turnover decisions, offering insights for faith-based institutions to strengthen retention through alignment of mission, culture, and supportive practices.